A noninferiority cluster randomised evaluation of a broflanilide indoor residual spraying insecticide, VECTRON T500, for malaria vector control in Tanzania - Njelembo J. Mbewe; Patrick K. Tungu; Louisa A. Messenger; John Bradley; Peter E. Mangesho; Boniface Shirima; Oliver Moshi; Magreth F. Shayo; Mohammed Seif; Natalie M. Portwood; Janneke Snetselaar; Salum Azizi; et al. (Scientific Reports)
Abstract Effective malaria vector control is being undermined by the rapid spread of insecticide resistance. VECTRON T500, a new indoor residual spraying (IRS) product containing the active ingredient broflanilide as a 50% wettable powder (WP), was previously shown to be efficacious in experimental hut trials. A two-arm non-inferiority cluster randomized controlled community trial was conducted in Muheza District, Tanga Region, Tanzania. VECTRON T500 was compared to the IRS product Fludora Fusion (clothianidin 50% + deltamethrin 6.25% WP-SB). Sixteen village clusters were pair-matched on baseline vector densities and allocated to reference and intervention arms. Monthly CDC light trapping sampled mosquitoes to estimate vector density, indoor biting, sporozoite and entomological inoculation rate (EIR). The non-inferiority margin of mosquito density was defined as a density ratio of 1.5. Susceptibility to IRS active ingredients was assessed in one of the local vectors, Anopheles gambiae sensu lato (s.l.), using WHO/CDC bottle bioassays. The residual efficacy of both IRS products was monitored for 12 months using susceptible and pyrethroid resistant An. gambiae sensu stricto (s.s.) mosquitoes. This study is registered with ClinicalTrials.gov (NCT05150808). A total of 916 and 844 houses were sprayed with Fludora Fusion and VECTRON T500, respectively, with equitable spray coverage. An. gambiae s.l. was resistant to deltamethrin but susceptible to clothianidin and broflanilide. The density ratio adjusted for baseline Anopheline mosquito density was 0.77 (95% CI: 0.45–1.29). The baseline adjusted sporozoite rate and EIR differences between the two trial arms were 0.84% and 15.61%, respectively. The residual efficacy was > 80% mortality for VECTRON T500 and Fludora Fusion, on both mud and concrete walls, 12 months post spraying. VECTRON T500 was non-inferior to Fludora Fusion in terms of its ability to reduce vector density, sporozoite rate and EIR, providing an additional vector control tool with a new mode of action for malaria prevention and insecticide resistance management.